1998
DOI: 10.1002/(sici)1098-2264(199806)22:2<105::aid-gcc4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis of consistent abnormalities at 8q12-q22 in breast cancer

Abstract: Studies using comparative genomic hybridization (CGH) indicate that portions of chromosome arm 8q from 8q12 to 8qter are present at an increased relative copy number in a broad range of solid tumors. In this study we define an ∼ 1 Mb wide region that appears to be frequently abnormal in copy number or structure in breast cancer cell lines and primary tumors. This was accomplished by fluorescence in situ hybridization (FISH) with yeast artificial chromosomes (YACs) mapped to 8q12‐q22. Eleven breast cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…The hD52 locus was mapped with respect to a YAC contig map spanning regions of an 8q12–q22 breast cancer amplicon (Schoenberg Fejzo et al, 1998) to determine whether hD52 is consistently included in chromosomal aberrations encompassing this region. The hD52 gene was localized using PCR to YAC 936B3, found at 102 cM on chromosome 8 (Schoenberg Fejzo et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hD52 locus was mapped with respect to a YAC contig map spanning regions of an 8q12–q22 breast cancer amplicon (Schoenberg Fejzo et al, 1998) to determine whether hD52 is consistently included in chromosomal aberrations encompassing this region. The hD52 gene was localized using PCR to YAC 936B3, found at 102 cM on chromosome 8 (Schoenberg Fejzo et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The hD52 locus was mapped with respect to a YAC contig map spanning regions of an 8q12–q22 breast cancer amplicon (Schoenberg Fejzo et al, 1998) to determine whether hD52 is consistently included in chromosomal aberrations encompassing this region. The hD52 gene was localized using PCR to YAC 936B3, found at 102 cM on chromosome 8 (Schoenberg Fejzo et al, 1998). In this previous study, YAC 936B3 was shown to map within the amplicon peak at 8q12–q22 in the human breast cancer SK‐BR‐3 cell line, and distal to the translocation breakpoints identified in the breast cancer cell lines MCF7, BT‐474, and MDA‐MB‐361 (Schoenberg Fejzo et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PREX2 gene is located in a chromosomal region that has been linked to aggressive cancer and metastatic progression and is frequently amplified in breast and prostate cancers [147, 148]. Interestingly, analysis of a breast tumor dataset annotated for PI3K pathway alterations revealed a positive association between P-Rex2a and PTEN expression.…”
Section: P-rex Rac-gefs: Novel Players In Breast Cancermentioning
confidence: 99%
“…The JAB1/CSN5 locus is located on chromosome 8q13.1, a region that is frequently amplified in breast, prostate, colorectal and ovarian cancers [73-77], which has also been linked to aggressive cancer phenotypes and metastatic progression [10,78]. …”
Section: Introductionmentioning
confidence: 99%